On the 14C and 39Ar Distribution in the Central Arctic Ocean: Implications for Deep Water Formation - Schlosser, Peter; Kromer, Bernd; Östlund, Gote; Ekwurzel, Brenda; Bönisch, Gerhard; Loosli, H. H.; Purtschert, Roland (Radiocarbon, 1994)
We present ΔA14C and 39Ar data collected in the Nansen, Amundsen and Makarov basins during two expeditions to the central Arctic Ocean (RV Polarstern cruises ARK IV/3, 1987 and ARK VIII/3, 1991). The data are used, together with published Δ14C values, to describe the distribution of Δ14C in all major basins of the Arctic Ocean (Nansen, Amundsen, Makarov and Canada Basins), as well as the 39Ar distribution in the Nansen Basin and the deep waters of the Amundsen and Makarov Basins. From the combined Δ14C and 39Ar distributions, we derive information on the mean “isolation ages” of the deep and bottom waters of the Arctic Ocean. The data point toward mean ages of the bottom waters in the Eurasian Basin (Nansen and Amundsen Basins) of ca. 250-300 yr. The deep waters of the Amundsen Basin show slightly higher 3H concentrations than those in the Nansen Basin, indicating the addition of a higher fraction of water that has been at the sea surface during the past few decades. Correction for the bomb 14C added to the deep waters along with bomb 3H yields isolation ages for the bulk of the deep and bottom waters of the Amundsen Basin similar to those estimated for the Nansen Basin. This finding agrees well with the 39Ar data. Deep and bottom waters in the Canadian Basin (Makarov and Canada Basins) are very homogeneous, with an isolation age of ca. 450 yr. Δ14C and 39Ar data and a simple inverse model treating the Canadian Basin Deep Water (CBDW) as one well-mixed reservoir renewed by a mixture of Atlantic Water (29%), Eurasian Basin Deep Water (69%) and brine-enriched shelf water (2%) yield a mean residence time of CBDW of ca. 300 yr.